Offshoring and productivity revisited: A time-series analysis - Pablo Agnese (Institute for the Study of Labor (IZA), 2013)
The subject of offshoring and productivity has not yet received the attention it deserves. Here I propose a simple framework for estimating the contribution of these strategies to the growth rate of labor productivity from a time-series perspective. This framework is then used to assess the impact of offshoring on skill upgrading and the labor share. For both empirical questions I take up the study of a group of Japanese industries during the recent years of slow growth. The results should be interpreted with caution yet clearly suggest that offshoring can improve labor productivity in the Semiconductors industry. Moreover, offshoring is found to be the source of important changes among industries with different skills (skill upgrading) and an important factor behind the fall of the labor share.
Keywords: J23; J24; E25; 330; offshoring; labor productivity; skill upgrading; labor share